DEVELOPMENTAL PSYCHOLOGY : Historical and Philosophical Perspectives - Lerner, Richard M. (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2020)
Originally published in 1983, the purpose of this book was to discuss the relations between philosophy and developmental psychology, as those relations existed over the course of the history of the discipline and as they existed at that time. Although not all portions of developmental psychology are surveyed, major proponents of several key areas are represented (e.g. organismic developmental theory, stage theory, life-span-developmental psychology, and the ecological approach to development). In addition, discussion of many currently prominent issues are included (e.g. constancy and change in human development, the use of multivariate models and methods, the role of the context in individual development, and the use of developmental theory in public policy and political arenas). The diversity of approaches and of interests present in the book are representative of the breadth of theoretical and empirical interests found in developmental psychology at the time.